The relationship of Emirati women with Gulf drama - فوزيه أل علي (International Journal of Social Communication, 2018)
ABSTRCT The current study aims to examine the nature of the relationship between Emirati women and Gulf drama and the increasing role it plays in providing women with information and knowledge and enabling them to discover and satisfy their actual needs, by trying to determine the extent of dependability, exposure intensity and type of drama content that Khaliji women do consume. In addition, we attempt to explore the topology of the space that Khaliji drama dedicates to women's issues and problems and the image that it conveys about women and the effects of exposure to this type of mediatic content. This research derives its significance from the importance of Emirati women in their society, moreover, the current study is considered to be the first of its kind, since no previous study that approached the current topic was found, In parallel, the importance of the study stems from its quest to find out the type of relationship between Emirati women and the Khaliji drama, and habits and patterns of exposure, which will provide solid information and practical perceptions to the producers of Khaliji drama and permit them to identify the nature of patterns of exposure, and provides a solid ground for decision-makers, enabling them to gain sufficient knowledge of the role of Khaliji drama in the life of Emirati women. The objectives of the current study are determined as follows: Descovering the patterns of the Emirati woman’s exposure to the Khaliji Drama. Locating the reasons that drive the Emirati woman to expose to the Khaliji Drama, Knowing the satisfactions achieved by the Emirati woman as a result of being exposed to the Khaliji Drama contents, providing those, who are in charge of the satellite channels, with updated information on the relationship between the Emirati woman and the Khaliji Drama